Oral application of Escherichia coli bacteriophage: safety tests in healthy and diarrheal children from Bangladesh. (13th November 2016) - Sarker, Shafiqul Alam; Berger, Bernard; Deng, Ying; Kieser, Silas; Foata, Francis; Moine, Deborah; Descombes, Patrick; Sultana, Shamima; Huq, Sayeeda; Bardhan, Pradip Kumar; Vuillet, Valérie; Praplan, Fabienne; et al.
Summary: A T4‐like coliphage cocktail was given with different oral doses to healthy Bangladeshi children in a placebo‐controlled randomized phase I safety trial. Fecal phage detection was oral dose dependent suggesting passive gut transit of coliphages through the gut. No adverse effects of phage application were seen clinically and by clinical chemistry. Similar results were obtained for a commercial phage preparation (Coliproteus from Microgen/Russia). By 16S rRNA gene sequencing, only a low degree of fecal microbiota conservation was seen in healthy children from Bangladesh who were sampled over a time interval of 7 days suggesting a substantial temporal fluctuation of the fecal microbiota composition. Microbiota variability was not associated with the age of the children or the presence of phage in the stool. Stool microbiota composition of Bangladeshi children resembled that found in children of other regions of the world. Marked variability in fecal microbiota composition was also seen in 71 pediatric diarrhea patients receiving only oral rehydration therapy and in 38 patients receiving coliphage preparations or placebo when sampled 1.2 or 4 days apart respectively. Temporal stability of the gut microbiota should be assessed in case‐control studies involving children before associating fecal microbiota composition with health or disease phenotypes.